Problema Pengentasan Kemiskinan Di Tingkat Lokal: Pengalaman Kota Bandar Lampung - Syamsul Ma'arif (PUBLICA, 2012)
Local authonomy era provides big opportunity for the Local Government of Bandar Lampung to run development in accordance to the local character. Room of freedom that so big has encouraged The Local Government of Bandar Lampung to accelerate the progress target of economic development as well as to eradicate problem of poverty in the area. The Local Government of Bandar Lampung must make decision between choosing the growth strategy by emphasizing big scale economic sector or choosing the equity strategy by paying attention more to people oriented economic. As the result of scarcity of resources, the Local Government of Bandar Lampung finally choose the growth strategy.